2011
DOI: 10.1055/s-0031-1283054
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Innovations in Craniofacial Surgery

Abstract: Reconstructive surgery for complex craniofacial defects challenges even the most experienced surgeons. Preoperative reconstructive planning requires consideration of both functional and aesthetic properties of the mandible, orbit, and midface. Technological innovations allow for computer-assisted preoperative planning, computer-aided manufacturing of patient-specific implants (PSIs), and computer-assisted intraoperative navigation. Although many case reports discuss computer-assisted preoperative planning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 33 publications
0
44
1
3
Order By: Relevance
“…Compared to other studies of porous polyethylene outcomes, in which complication rates range from 10.3% to 26.3% (Baumann et al, 2002;Hollier et al, 2001;Rudman et al, 2011), the rate of complications reported in the present study is high (31.8%). A plausible explanation for this high rate of complications is the inclusion of patient dissatisfaction with the aesthetic result as a postoperative complication.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Compared to other studies of porous polyethylene outcomes, in which complication rates range from 10.3% to 26.3% (Baumann et al, 2002;Hollier et al, 2001;Rudman et al, 2011), the rate of complications reported in the present study is high (31.8%). A plausible explanation for this high rate of complications is the inclusion of patient dissatisfaction with the aesthetic result as a postoperative complication.…”
Section: Discussioncontrasting
confidence: 88%
“…The computer-assisted reconstruction of maxillofacial defects could provide a more predictable aesthetic outcome for patients using porous polyethylene implants. Although many case reports discuss computer-assisted preoperative planning and creation of custom implants, a general overview of computer-assisted innovations and their treatment outcomes is not readily available (Rudman et al, 2011). Hence, further research is needed to determine whether these technological advances can improve the aesthetic results of porous polyethylene implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virtual model is manufactured in a direct or indirect form (Ibrahim et al, 2009;Cantín et al, 2015). In surgery, medicine and odontology, the process on CAD begins with the computerized tomography of the patient (Rudman et al, 2011). The images used in this process require a compatibility with some shapes until the precision of the models are acceptable to the stereolithographic model (Ibrahim et al), although in the transfer and processing of information, for example in STL archives, there could exist a loss of data (Huotilainen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[4,5,[24][25][26] Preclinical planning studies for implementation and validation of tools for planning, design and adaptation of allograft into recipients are other key aspects for anatomical structures of donors and recipients are consistent in size and configuration to allow a reasonable accommodation. Anthropometric study of facial soft and hard tissues both the donor and the recipient must be as accurate as possible to ensure the viability of the procedure and the proper insertion of the allograft into the defect, [27][28][29] even including the preparation of preoperative surgical osteotomy guides. [30][31][32] …”
Section: Surgical Considerations Preclinical Modelsmentioning
confidence: 99%